2017
DOI: 10.1089/end.2016.0644
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and Electrohydraulic Shock Wave Lithotripsy-Induced Urothelial Damage: Is There a Difference?

Abstract: Purpose: To evaluate and compare the acute effect of electromagnetic and electrohydraulic extracorporeal shockwave lithotripsy (SWL) on the urothelial layers of kidney and ureter. Materials and Methods: Fifty patients, 29 males (58%) and 21 females (42%), with an average age of 51.68 years (range: 37-70) who underwent SWL application in two different centers were included. Twenty-eight patients (56%) were treated with electrohydraulic and 22 (44%) were treated with electromagnetic lithotripsy. Urinary cytologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…A possible limitation of the study is on the part of the operator: although all the centers have a high level of expertise, US targeting was performed by a single operator No significant differences in efficacy were demonstrated with the use of an electrohydraulic, electroconductive, and electromagnetic lithotripter, which is in agreement with the results of several studies [6][7] . However, a significant difference was observed when analgesic consumption was compared: it was significantly higher in the electrohydraulic type than in the electromagnetic generator type with fluoroscopy guidance.…”
Section: Discussionsupporting
confidence: 81%
“…A possible limitation of the study is on the part of the operator: although all the centers have a high level of expertise, US targeting was performed by a single operator No significant differences in efficacy were demonstrated with the use of an electrohydraulic, electroconductive, and electromagnetic lithotripter, which is in agreement with the results of several studies [6][7] . However, a significant difference was observed when analgesic consumption was compared: it was significantly higher in the electrohydraulic type than in the electromagnetic generator type with fluoroscopy guidance.…”
Section: Discussionsupporting
confidence: 81%
“…In another human study comparing electromagnetic versus electrohydraulic lithotriptors, it has been reported that electromagnetic lithotriptor caused higher number of red blood cells in the urine compared to electrohydraulic lithotriptor in the early post-SWL period. However, cytologic evaluations performed 10 days after SWL therapy showed recovery of all abnormal cytologic findings (10). On the other hand, an intraparenchymal, subcapsular and perirenal hematoma is another well-known ESWL-induced acute renal complication.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have compared the efficacies of electrohydraulic and electromagnetic ESWT for treating ureter stones, the results obtained with the 2 types of generators were not significantly different [ 29 30 ]. However, we anticipate that electromagnetic ESWT will be found to have theoretical advantages that could be applicable in clinical practice in the future.…”
Section: Discussionmentioning
confidence: 99%